Public perception of the wood products industry in Malaysia and its implication on the future workforce - Ratnasingam, Jegatheswaran; Ab Latib, Hazirah; Liat, Lim Choon; Mariapan, Manohar; Jegatheswaran, Natkuncaran; Othman, Kamaruzaman; Amir, Mohd Afthar (2022)
Despite contributing almost RM 20 billion (USD 4.9 billion) in exports earnings annually, the public perception of the wood products industry in Malaysia remains unknown. Therefore, this study attempted to assess public perceptions about the industry in Malaysia among the public, including teenagers, based on 3,010 reliably answered questionnaire-surveys. Generally, the public perceived the wood products industry to be a low-wage economy, labor-intensive, predominated by foreign contract workers, and unsustainable in the long-term. In essence, the public appear to have stronger negative images of the industry compared to the positive images. The main drivers for such negative perceptions, identified through the factor analysis, were the prevailing business environment in the industry and its workforce characteristics. Consequently, teenagers and school-leavers tend to be less interested in pursuing a career in the industry, let alone pursuing further studies in the wood-related fields. The main reasons cited for this were the limited career growth opportunity due to the predomination of family-controlled small and medium-sized enterprises (SMEs) in the industry and the discouragements from family members and friends. The provision of reliable, timely, and transparent information is important to boost the public’s awareness and build positive beliefs and perception of the wood industry.